As condições de competitividade e a viabilidade das estratégias de diferenciação no setor de produtos asfálticos nos estados da Bahia, Sergipe, Alagoas e Pernambuco: um estado comparativo entre duas empresas do setor - Barreto, César Santos (2007)
This dissertation was intended to analyze the evolution of the competition conditions of asphalt distribution s sector at the states of Bahia, Sergipe, Alagoas and Pernambuco identifying the market segments and the competitive logic that they follow. Then, were analyzed the strategies adopted by two players of the sector and their efficacy, to clarify if the strategies based on complementary services adopted to differentiate asphalts have provided better results in market-share, sales, level of fidelity and quality of service. For this, first, a research was done at Petrobras the only enterprise that products asphalt , and a comparative study between the two players chosen. Besides, researches were done with clients of these players to identify the complementary services that are considered important for them. The research showed that both players use strategies based on development of products and offering of complementary services, but these last strategies seem to be more tactical and operational than really strategic. These actions appeared useful to catch and keep clients, but not decisive, which was corroborated for the reduction of the product sales profits. It was possible to realize that clients consider some of these actions important to the definition of a supplier of this kind of product, but they do not consider it a strong reason to get fidelity with any supplier. This can show that is necessary to increase the relationship with the clients to identify other things that are important to them to choose a supplier of asphalt, and to develop strategies really new that can asseverate a position of vanguard for a long time.